Hubungan Antara Status Kemoterapi , Jumlah Netrofil dengan IgM dan IgG Antimannan pada Pasien Kanker Paru yang Mengalami Kolonisasi Candida spp - Chozin, Iin Noor; Setyawan, Ungky; Rakhma, Sastia (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Background: The diagnosis Candidiasis spp in patients with lung Cancer is difficult. It is related to immunocompromised status. Antimannan IgM and IgG biomarkers are used to diagnose candidiasis. The aim of this study is to determine the correlation between chemotherapy status, absolute neutrophyl count to antimannan IgM and IgG. Methods: The study design was a cross-sectional correlative analytic which included 37 patients in inpatient ward of Dr. Saiful Anwar Hospital Malang. The inclusion criteria patients aged >18 years with lung cancer who had established anatomical pathology, both non-small cell lung cancer and small cell lung cancer, and on sputum culture examination Candida spp grew with or without the growth of colonies of fungal species nor bacterial colonies. Exclusion criteria included lung cancer patients with HIV infection and autoimmune disease. Of the 37 patients who had received chemotherapy and had not received chemotherapy. The absolute neutrophil count and IgM and IgG antimannan were examined. Data chemotherapy status, absolute neutrophil count were analyzed in relation to IgM and IgG antimannan antibodies. Results: This study showed that there were not correlation between chemotherapy status with antimannan IgM (p=0.585; r=0.089) nor IgG (p=0.124; r=0.245). However, there was a positive, moderate correlation between absolute neutrophil count and antimannan IgM (p=0,042; r=0,362), but there is no correlation between absolute neutrophil count and antimannan IgG (p=0,094;r=0,277). Conclusion: There is positive moderate correlation between IgM antimannan with absolute neutropil count but no correlation with IgG antimannan. There is no correlation between IgM and IgG antimannan with chemotherapy status.